Composition of Broken Ridge samples (Table 1) - Ian L Gibson (PANGAEA, 1991)
The Broken Ridge tilted and truncated sequence of middle Eocene to Turanian calcareous sediments with intercalated basaltic ash layers is characterized by diagenetic alteration. The level at which opal-CT forms from volcanic glass and the opal-CT/quartz boundary shows that this alteration increases in intensity with stratigraphic depth and is not related to depth below the seafloor. Thus, the rocks were altered before they were tilted and truncated. The preservation of the pre-rift alteration history may be a function of the rapid uplift and erosion following the initiation of spreading between Broken Ridge and the Kerguelen Plateau. The geothermal gradient at the time of rifting, deduced from the pattern of silica diagenesis, agrees with results from present-day heat-flow measurements and suggests that there was no large thermal anomaly at Broken Ridge that time.
Supplement to: Gibson, IL (1991): Diagenesis, heat flow, and rifting at Broken Ridge, Indian Ocean. In: Weissel, J; Peirce, J; Taylor, E; et al. (eds.), Proceedings of the Ocean Drilling Program, Scientific Results, College Station, TX (Ocean Drilling Program), 121, 519-523, https://doi.org/10.2973/odp.proc.sr.121.164.1991